Peramalan Ekspor Karet Provinsi Jambi dengan Model Seasonal ARIMA - Atmanegara, Eviyana (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2022)
The industrial sector contributed the most to total non-oil and gas exports in Jambi Province. Rubber and its processed products are the main export commodities in the industrial sector. The export value of rubber and its products increased in 2017 but decreased again from 2018 to 2020. The decline in exports harmed the economy in Jambi Province. It is necessary to predict the export value of rubber and its products in the coming period. Forecasting is done on time series data using the ARIMA and SARIMA models. The best model for modeling the export value of rubber and its products in Jambi Province is SARIMA (0,1,1)(0,0,1)12. It is predicted that the export value of rubber and its processed products will decrease by around 4 percent in 2022. And decrease by around 5 percent in 2023. The results of this forecast can be used as an early warning in making policies related to exports in the coming period.